Bone filler containing magnetic calcium salt and preparation method

CN119587749AActive Publication Date: 2025-03-11TIANJIN UNIV

Patent Information

Application Number
CN202411458123.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-18
Publication Date
2025-03-11
Estimated Expiration
2044-10-18

AI Technical Summary

Technical Problem

In the treatment of bone tumors, existing bone cement materials have problems such as excessive heating rate, poor water rupture resistance, and lack of antibacterial properties, which are difficult to meet the needs of auxiliary treatment after bone tumor surgery.

Method used

Calcium oxide/ferrous tetraoxide complex was prepared as magnetic calcium salt by suspended emulsion dispersion method, combined with sodium carboxymethylcellulose solution containing disodium hydrogen phosphate, and a bone filler with a moderate magnetothermal heating rate, water crumbness and antibacterial properties were prepared by mixing the specific powder and liquid ratio.

Benefits of technology

The magnetothermal treatment effect of bone filler is achieved, the risk to other tissues is reduced, and it has good anti-water crumbness and antibacterial properties, which is suitable for the treatment and repair of bone tumors.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119587749A_ABST
    Figure CN119587749A_ABST
Patent Text Reader

Abstract

The invention relates to a magnetic calcium salt-containing bone filler and a preparation method thereof, the bone filler is blocky and is prepared by blending powder and liquid according to a ratio of 2: 1g / mL, preparing and curing; the powder comprises the following components in percentage by mass: 61.5 to 81.7 percent of calcium sulfate and 18.3 to 38.5 percent of magnetic calcium salt; the liquid is a sodium carboxymethyl cellulose solution containing disodium hydrogen phosphate, the mass percentage content of the disodium hydrogen phosphate is 0.16-2.52%, and the mass percentage content of the sodium carboxymethyl cellulose is 1.15-4.25%. The bone filler containing the magnetic calcium salt has the advantages of being moderate in magnetic heating rate, resistant to water collapse and degradable and absorbable.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of biomedical materials, and in particular relates to a bone filler containing magnetic calcium salt and a preparation method thereof. Background Art

[0002] When the bone defect reaches a critical size, bone transplantation is usually required for treatment. The most commonly used bone repair material at this stage is bone cement. This type of material is usually formed by mixing solid and liquid phases and then solidifying. It is a biomaterial with self-solidifying properties. It can be shaped arbitrarily before solidification, and can be injected to achieve minimally invasive surgery, which is very conducive to operation. Therefore, it is widely welcomed by surgeons in clinical practice and has become a highly used orthopedic biomaterial. The ideal bone cement material should have good biocompatibility, promote new bone formation, and be completely degraded and absorbed by itself. Its mechanical properties should be similar to or better than natural bone. The most commonly used bone cement material is inorganic bone cement such as calcium phosphate or calcium sulfate. Calcium phosphate bone cement can be degraded and absorbed after implantation, but it has the characteristic of easy disintegration. For bone defects caused by bone tumors or bone metastasis of malignant tumors, while surgically removing the bone tumor, other means such as chemotherapy and radiotherapy must be used for postoperative treatment. Inorganic bone cements such as calcium phosphate also lack the means of assisting subsequent treatment. Many scholars have used bone repair materials with magnetic functional phases to repair bone tissue during bone tumor surgery, and to assist in the treatment of bone tumors with magnetic hyperthermia to prevent tumor recurrence and metastasis, which has become a new treatment method in the field of bone tumor treatment. The most commonly used magnetic material is Fe3O4 magnetic powder, such as YMatsumine, etc. Calcium phosphate bone cement is used as the matrix, and Fe3O4 is introduced into it to prepare magnetic bone cement. After the material is implanted into the bone, the surface temperature of the cortical bone can reach 40°C within 2 minutes under a 1.5MHz magnetic field. He Shuli and others have also invented high-heat-yielding magnetic bone cements with cobalt ferrite, manganese ferrite and zinc ferrite as magnetic functional phases. However, bone filling materials or bone cements with added magnetic ferroferric oxide have the problem of too fast heating rate, and the extreme temperature can reach 500°C, which poses a risk of burning other tissues. In addition, the added bone grafting material has no antibacterial properties, and antibiotics need to be added separately or antibacterial elements such as silver need to be introduced to assist in antibacterial treatment. Summary of the invention

[0003] In view of the deficiencies of the prior art, the present invention provides a bone filler containing magnetic calcium salt, which has moderate magnetic thermal heating rate, is resistant to water disintegration, and is degradable and absorbable, and a preparation method thereof.

[0004] One of the above objects of the present invention is achieved by the following technical solution:

[0005] A bone filler containing magnetic calcium salt is in block shape and is prepared by mixing and solidifying powder and liquid in a ratio of 2:1 g / mL; the powder components and their mass percentages are: 61.5-81.7% calcium sulfate and 18.3-38.5% magnetic calcium salt; the liquid is a sodium carboxymethyl cellulose solution containing disodium hydrogen phosphate, the mass percentage of the disodium hydrogen phosphate is 0.16-2.52%, and the mass percentage of the sodium carboxymethyl cellulose is 1.15-4.25%.

[0006] Moreover, the magnetic calcium salt is a calcium oxide / ferroferric oxide complex, the mass percentage of calcium oxide in the magnetic calcium salt is 22-47%, and the mass percentage of ferroferric oxide in the magnetic calcium salt is 53-78%;

[0007] Moreover, the particle size distribution of the magnetic calcium salt ranges from 2.7 to 83 μm;

[0008] Moreover, the calcium sulfate is a mixture of calcium sulfate hemihydrate and calcium sulfate dihydrate, wherein the mass percentage of calcium sulfate hemihydrate is 70-95%, and the rest is calcium sulfate dihydrate.

[0009] The second object of the present invention is achieved by the following technical solution:

[0010] A method for preparing the above-mentioned bone filler containing magnetic calcium salt comprises the following steps:

[0011] Step 1, preparing a sodium carboxymethyl cellulose solution with a mass percentage of 3.28-6.52%, and then adding iron powder to the sodium carboxymethyl cellulose solution to prepare an iron powder suspension, wherein the mass percentage of the iron powder to the sodium carboxymethyl cellulose solution is (0.35-1.11):1;

[0012] Step 2, preparing a sodium hydroxide solution with a mass percentage of 10.7-47.3%, and preparing a calcium chloride solution with a mass percentage of 14.2-42.5%;

[0013] Step 3, adding the iron powder suspension prepared in step 1 to the sodium hydroxide solution prepared in step 2, the volume ratio of the two being 1:3; then adding the calcium chloride solution prepared in step 2 to the iron powder / sodium carboxymethyl cellulose / sodium hydroxide solution at a rate of 1.5-24 mL / min, the volume ratio of the calcium chloride solution to the sodium hydroxide solution being 1:2;

[0014] Step 4, continue stirring and reacting for 20-60 minutes to obtain an iron / calcium hydroxide suspension, and filter and wash to obtain an iron / calcium hydroxide precipitate;

[0015] Step 5, calcining the precipitate at 530-590° C. for 15-120 min, transferring it to a dryer and cooling it to room temperature; crushing and grinding to obtain a magnetic calcium salt with controllable particle size and morphology;

[0016] Step 6, uniformly mixing a certain amount of magnetic calcium salt and a certain amount of calcium sulfate to obtain a powder;

[0017] Step 7, preparing a sodium carboxymethyl cellulose solution containing disodium hydrogen phosphate, wherein the mass percentage of disodium hydrogen phosphate is 0.16-2.52%, and the mass percentage of sodium carboxymethyl cellulose is 1.15-4.25%;

[0018] Step 8: Add liquid to the evenly mixed powder in a ratio of 2:1 g / mL and stir.

[0019] After 10 to 60 seconds, apply it to the mold with the reserved hole, and after curing for 10 to 20 minutes, demould to obtain the bone filler containing magnetic calcium salt.

[0020] The advantages and positive effects of the present invention are:

[0021] 1. The present invention prepares the calcium hydroxide / iron complex by the method of suspension emulsion dispersion, which solves the problem of uneven mixing when iron or iron oxide is directly added to the calcium salt powder. The viscous liquid of sodium carboxymethyl cellulose is equivalent to the emulsion, which enhances the surface tension of water, hinders the speed of calcium ions and hydroxide ions combining to form precipitation, and forms regular micron particles based on iron suspension particles. Then, through high-temperature combustion and calcination, calcium hydroxide is converted into calcium oxide and decomposes water vapor. At the same time, the iron powder reacts with oxygen and water vapor at high temperature to convert into ferroferric oxide, and obtains uniform particles of calcium oxide / ferroferric oxide magnetic calcium salt.

[0022] 2. The liquid of the present invention adopts an alkaline solution of sodium carboxymethyl cellulose containing disodium hydrogen phosphate to enhance the water disintegration resistance of the bone filler. The powder and liquid are blended in a ratio of 2:1 (g / mL) and applied to prepare a block bone filler of a specific shape. During the curing process, the calcium oxide in the magnetic calcium salt reacts with water and disodium hydrogen phosphate to produce part of calcium phosphate and calcium hydroxide, and the ferroferric oxide particles are coated to finally obtain a new bone filler of calcium sulfate / ferroferric oxide / calcium hydroxide / calcium phosphate. The calcium sulfate, calcium phosphate and other substances contained in the bone filler can be gradually degraded and absorbed, and at the same time, calcium hydroxide can play an antibacterial role, giving the bone filler containing the magnetic calcium salt an antibacterial effect.

[0023] 3. The magnetic calcium salt prepared by the present invention can give bone fillers a certain degree of magnetism, and can heat bone fillers through alternating magnetic fields and hysteresis, thereby killing or eliminating tumors and achieving high-temperature sterilization. The calcium hydroxide produced at the same time also has a certain degree of antibacterial properties, and can reduce the heating rate of Fe3O4 under an alternating magnetic field. In vitro studies have shown that its temperature rises to 95.9°C, which is close to the in vitro polymerization temperature of 90°C of general PMMA bone cement, and is much lower than the 500°C of pure ferroferric oxide, reducing the risk of burning other tissues. The strength of the prepared new bone filler meets the strength of cancellous bone, and can be used for the fixation of various non-load-bearing fracture sites and the filling of bone defects. BRIEF DESCRIPTION OF THE DRAWINGS

[0024] Figure 1 is the XRD pattern of the magnetic calcium salt prepared in Example 1 of the present invention;

[0025] Figure 2 From left to right are the temperature rise results of the bone fillers tested in Example 1, Example 3, and Example 6 under a magnetic field;

[0026] Figure 3 From left to right are the results of the compression strength of the bone fillers tested in Example 1, Example 2, Example 4, and Example 5;

[0027] Figure 4 This is a picture of an immersion test of the bone filler of Example 1 of the present invention;

[0028] Figure 5 It is a graph showing the degradation test of the bone filler in Example 6 of the present invention. DETAILED DESCRIPTION

[0029] The structure of the present invention is further described below with reference to the accompanying drawings and by way of examples. It should be noted that the present examples are descriptive rather than restrictive.

[0030] A bone filler containing magnetic calcium salt, the bone filler is a block of a specific shape, prepared by mixing and solidifying powder and liquid in a ratio of 2:1 (g / mL);

[0031] The powder comprises 18.3-38.5% by weight of magnetic calcium salt and 61.5-81.7% by weight of calcium sulfate; the liquid used is a sodium carboxymethyl cellulose solution containing disodium hydrogen phosphate, wherein the mass percentage of the disodium hydrogen phosphate is 0.16-2.52% and the mass percentage of the sodium carboxymethyl cellulose is 1.15-4.25%; in the magnetic calcium salt, the mass percentage of calcium oxide in the magnetic calcium salt is 22-47% and the mass percentage of ferrosoferric oxide in the magnetic calcium salt is 53-78%; the particle size distribution range of the magnetic calcium salt is 2.7-83 mu m; in the calcium sulfate, the mass percentage of calcium sulfate hemihydrate in the calcium sulfate is 70-95% and the rest is calcium sulfate dihydrate.

[0032] The preparation method of the bone filler containing magnetic calcium salt of the present invention is as follows:

[0033] Step 1, preparing a sodium carboxymethyl cellulose solution with a mass percentage of 3.28-6.52%, and then adding iron powder to the sodium carboxymethyl cellulose solution to prepare an iron powder suspension, wherein the mass percentage of the iron powder to the sodium carboxymethyl cellulose solution is (0.35-1.11):1;

[0034] Step 2, preparing a sodium hydroxide solution with a mass percentage of 10.7-47.3%, and preparing a calcium chloride solution with a mass percentage of 14.2-42.5%;

[0035] Step 3, adding the iron powder suspension prepared in step 1 to the sodium hydroxide solution prepared in step 2, the volume ratio of the two being 1:3; then adding the calcium chloride solution prepared in step 2 to the iron powder / sodium carboxymethyl cellulose / sodium hydroxide solution at a rate of 1.5-24 mL / min, the volume ratio of the calcium chloride solution to the sodium hydroxide solution being 1:2;

[0036] Step 4, continue stirring and reacting for 20-60 minutes to obtain an iron / calcium hydroxide suspension, and filter and wash to obtain an iron / calcium hydroxide precipitate;

[0037] Step 5, calcining the precipitate at 530-590° C. for 15-120 min, transferring it to a dryer and cooling it to room temperature; crushing and grinding to obtain a magnetic calcium salt with controllable particle size and morphology;

[0038] Step 6, uniformly mixing a certain amount of magnetic calcium salt and a certain amount of calcium sulfate to obtain a powder;

[0039] Step 7, preparing a sodium carboxymethyl cellulose solution containing disodium hydrogen phosphate, wherein the mass percentage of disodium hydrogen phosphate is 0.16-2.52%, and the mass percentage of sodium carboxymethyl cellulose is 1.15-4.25%;

[0040] Step 8: Add the evenly mixed powder to the liquid in a ratio of 2:1 g / mL, stir for 10 to 60 seconds, apply it to the mold with the reserved hole, and solidify for 10 to 20 minutes before demoulding to obtain the bone filler. The shape of the bone filler can be a cube, a cuboid, a cylinder, etc.

[0041] Example 1

[0042] A bone filler containing magnetic calcium salt is a φ6×12mm cylinder, which is prepared by mixing and solidifying powder and liquid in a ratio of 2:1 (g / mL);

[0043] The powder is 38.5% by weight of magnetic calcium salt and 61.5% by weight of calcium sulfate; the liquid is 2.52% disodium hydrogen phosphate sodium carboxymethyl cellulose solution, and the mass percentage of sodium carboxymethyl cellulose is 4.25%; in the magnetic calcium salt, calcium oxide accounts for 47% by weight of the magnetic calcium salt, and ferrosoferric oxide accounts for 53% by weight of the magnetic calcium salt; the particle size distribution range of the magnetic calcium salt is 2.7-83 μm; in the calcium sulfate, calcium sulfate hemihydrate accounts for 70% by weight of the calcium sulfate, and calcium sulfate dihydrate accounts for 30% by weight;

[0044] The preparation method of the bone filler in this embodiment is as follows:

[0045] (1) preparing a sodium carboxymethyl cellulose solution with a mass percentage of 3.28%, and then adding iron powder to the sodium carboxymethyl cellulose solution to prepare an iron powder suspension, wherein the mass percentage of the iron powder to the sodium carboxymethyl cellulose solution is 0.35:1;

[0046] (2) preparing a sodium hydroxide solution having a mass percentage of 47.3% and a calcium chloride solution having a mass percentage of 42.5%;

[0047] (3) adding 40 mL of the prepared iron powder suspension to 120 mL of the prepared sodium hydroxide solution; then adding 60 mL of the prepared calcium chloride solution to the iron powder / sodium carboxymethyl cellulose / sodium hydroxide solution at a rate of 24 mL / min;

[0048] (4) continuing to stir the reaction for 60 min to obtain an iron / calcium hydroxide suspension, and filtering and washing to obtain an iron / calcium hydroxide precipitate;

[0049] (5) calcining the precipitate at 530° C. for 120 min, transferring it to a dryer and cooling it to room temperature; crushing and grinding the precipitate to obtain a magnetic calcium salt with controllable particle size and morphology;

[0050] (6) uniformly mixing a certain amount of magnetic calcium salt and a certain amount of calcium sulfate to obtain a powder;

[0051] (7) preparing a sodium carboxymethyl cellulose solution containing disodium hydrogen phosphate, wherein the mass percentage of disodium hydrogen phosphate is 2.52% and the mass percentage of sodium carboxymethyl cellulose is 4.25%;

[0052] (8) The uniformly mixed powder is added to the liquid in a powder to liquid ratio of 2:1 (g / mL), stirred for 60 seconds, applied to the mold with the reserved hole, and demolded after curing for 10 minutes to obtain a bone filler containing magnetic calcium salt.

[0053] The magnetic calcium salt prepared in Example 1 was scanned by XRD. Figure 1As shown, the diffraction peaks are mainly those of ferroferric oxide and calcium oxide, indicating that the main component of the magnetic calcium salt is a complex of ferroferric oxide and calcium oxide;

[0054] The bone filler of Example 1 was subjected to a magnetothermal test on bone cement under an alternating magnetic field of 50 KHZ. Figure 2 As shown, the magnetic thermal temperature of the bone filler containing magnetic calcium salt can reach 95.9°C in 1 minute, which meets the requirement that the magnetic thermal treatment temperature is greater than 40°C.

[0055] The bone filler of Example 1 was subjected to a compressive strength test. Figure 3 As shown, the compressive strength of the bone filler containing magnetic calcium salt is 11.72MPa, which meets the requirement of cancellous bone strength range of 2-10MPa.

[0056] The bone filler of Example 1 was placed in a phosphate buffer solution. Figure 4 As shown, after standing for 24 hours, the solution was clear and no bone filler was found to fall off or peel off, indicating that the bone filler containing magnetic calcium salt has good resistance to water disintegration.

[0057] Example 2

[0058] A bone filler containing magnetic calcium salt is a φ6×12mm cylinder, which is prepared by mixing and solidifying powder and liquid in a ratio of 2:1 (g / mL);

[0059] The powder is 20% by weight of magnetic calcium salt and 80% by weight of calcium sulfate; the liquid is 0.16% sodium hydrogen phosphate sodium carboxymethyl cellulose solution, and the mass percentage of sodium carboxymethyl cellulose is 2.10%; in the magnetic calcium salt, calcium oxide accounts for 35% by weight of the magnetic calcium salt, and ferrosoferric oxide accounts for 65% by weight of the magnetic calcium salt; the particle size distribution range of the magnetic calcium salt is 5-53 μm; in the calcium sulfate, calcium sulfate hemihydrate accounts for 90% by weight of the calcium sulfate, and calcium sulfate dihydrate accounts for 10% by weight;

[0060] The preparation method of the bone filler in this embodiment is as follows:

[0061] (1) preparing a sodium carboxymethyl cellulose solution with a mass percentage of 6.52%, and then adding iron powder to the sodium carboxymethyl cellulose solution to prepare an iron powder suspension, wherein the mass percentage of the iron powder to the sodium carboxymethyl cellulose solution is 0.73:1;

[0062] (2) preparing a sodium hydroxide solution having a mass percentage of 42.5% and a calcium chloride solution having a mass percentage of 41.5%;

[0063] (3) adding 40 mL of the prepared iron powder suspension to 120 mL of the prepared sodium hydroxide solution; then adding 60 mL of the prepared calcium chloride solution to the iron powder / sodium carboxymethyl cellulose / sodium hydroxide solution at a rate of 6 mL / min;

[0064] (4) continuing to stir the reaction for 45 min to obtain an iron / calcium hydroxide suspension, which was filtered and washed to obtain an iron / calcium hydroxide precipitate;

[0065] (5) calcining the precipitate at 590° C. for 30 min, transferring it to a dryer and cooling it to room temperature; crushing and grinding the precipitate to obtain a magnetic calcium salt with controllable particle size and morphology;

[0066] (6) uniformly mixing a certain amount of magnetic calcium salt and a certain amount of calcium sulfate to obtain a powder;

[0067] (7) preparing a sodium carboxymethyl cellulose solution containing disodium hydrogen phosphate, wherein the mass percentage of the disodium hydrogen phosphate is 0.16% and the mass percentage of the sodium carboxymethyl cellulose is 2.10%;

[0068] (8) The uniformly mixed powder is added to the liquid in a powder to liquid ratio of 1:1 (g / mL), stirred for 60 seconds, applied to the mold with the reserved hole, and demolded after curing for 15 minutes to obtain a bone filler containing magnetic calcium salt.

[0069] The bone filler of Example 2 was tested for compressive strength. The compressive strength of the bone filler containing magnetic calcium salt was 11.26 MPa, which met the requirement of cancellous bone strength range of 2-10 MPa.

[0070] Example 3

[0071] A bone filler containing magnetic calcium salt is a φ6×12mm cylinder, which is prepared by mixing and solidifying powder and liquid in a ratio of 2:1 (g / mL);

[0072] The powder is 18.3% by weight of magnetic calcium salt and 81.7% by weight of calcium sulfate; the liquid is 1.50% disodium hydrogen phosphate sodium carboxymethyl cellulose solution, and the mass percentage of sodium carboxymethyl cellulose is 1.15%; in the magnetic calcium salt, calcium oxide accounts for 22% by weight of the magnetic calcium salt, and ferrosoferric oxide accounts for 78% by weight of the magnetic calcium salt; the particle size distribution range of the magnetic calcium salt is 5-45 μm; in the calcium sulfate, the mass percentage of calcium sulfate hemihydrate accounts for 95% of the calcium sulfate, and the mass percentage of calcium sulfate dihydrate is 5%;

[0073] The preparation method of the bone filler in this embodiment is as follows:

[0074] (1) preparing a sodium carboxymethyl cellulose solution with a mass percentage of 4.50%, and then adding iron powder to the sodium carboxymethyl cellulose solution to prepare an iron powder suspension, wherein the mass percentage of the iron powder to the sodium carboxymethyl cellulose solution is 0.38:1;

[0075] (2) preparing a sodium hydroxide solution having a mass percentage of 10.7% and a calcium chloride solution having a mass percentage of 14.2%;

[0076] (3) adding 40 mL of the prepared iron powder suspension to 120 mL of the prepared sodium hydroxide solution; then adding 60 mL of the prepared calcium chloride solution to the iron powder / sodium carboxymethyl cellulose / sodium hydroxide solution at a rate of 4.5 mL / min;

[0077] (4) continuing to stir the reaction for 20 min to obtain an iron / calcium hydroxide suspension, which was filtered and washed to obtain an iron / calcium hydroxide precipitate;

[0078] (5) calcining the precipitate at 550° C. for 15 min, transferring it to a dryer and cooling it to room temperature; crushing and grinding the precipitate to obtain a magnetic calcium salt with controllable particle size and morphology;

[0079] (6) uniformly mixing a certain amount of magnetic calcium salt and a certain amount of calcium sulfate to obtain a powder;

[0080] (7) preparing a sodium carboxymethyl cellulose solution containing disodium hydrogen phosphate, wherein the mass percentage of disodium hydrogen phosphate is 1.50% and the mass percentage of sodium carboxymethyl cellulose is 1.15%;

[0081] (8) The uniformly mixed powder was added with liquid in a powder to liquid ratio of 2:1 (g / mL), stirred for 30 seconds, and solidified for 20 minutes before demolding to obtain a bone filler containing magnetic calcium salt.

[0082] The bone filler of Example 3 was subjected to a magnetothermal test on bone cement in an alternating magnetic field of 50KHZ. The magnetothermal temperature of the bone filler could reach 84.5°C in 1 minute, which met the requirement that the magnetothermal treatment temperature should be greater than 40°C.

[0083] Example 4

[0084] A bone filler containing magnetic calcium salt is a φ6×12mm cylinder, which is prepared by mixing and solidifying powder and liquid in a ratio of 2:1 (g / mL);

[0085] The powder is 30% by weight of magnetic calcium salt and 70% by weight of calcium sulfate; the liquid is 0.65% sodium hydrogen phosphate sodium carboxymethyl cellulose solution, and the mass percentage of sodium carboxymethyl cellulose is 3.10%; in the magnetic calcium salt, calcium oxide accounts for 44% by weight of the magnetic calcium salt, and ferrosoferric oxide accounts for 56% by weight of the magnetic calcium salt; the particle size distribution range of the magnetic calcium salt is 10-83 μm; in the calcium sulfate, calcium sulfate hemihydrate accounts for 80% by weight of the calcium sulfate, and calcium sulfate dihydrate accounts for 20% by weight;

[0086] The preparation method of the bone filler in this embodiment is as follows:

[0087] (1) preparing a sodium carboxymethyl cellulose solution with a mass percentage of 4.0%, and then adding iron powder to the sodium carboxymethyl cellulose solution to prepare an iron powder suspension, wherein the mass percentage of the iron powder to the sodium carboxymethyl cellulose solution is 0.42:1;

[0088] (2) preparing a sodium hydroxide solution having a mass percentage of 35.0% and a calcium chloride solution having a mass percentage of 42.5%;

[0089] (3) adding 40 mL of the prepared iron powder suspension to 120 mL of the prepared sodium hydroxide solution; then adding 60 mL of the prepared calcium chloride solution to the iron powder / sodium carboxymethyl cellulose / sodium hydroxide solution at a rate of 21 mL / min;

[0090] (4) continuing to stir the reaction for 60 min to obtain an iron / calcium hydroxide suspension, and filtering and washing to obtain an iron / calcium hydroxide precipitate;

[0091] (5) calcining the precipitate at 570° C. for 60 min, transferring it to a dryer and cooling it to room temperature; crushing and grinding the precipitate to obtain a magnetic calcium salt with controllable particle size and morphology;

[0092] (6) uniformly mixing a certain amount of magnetic calcium salt and a certain amount of calcium sulfate to obtain a powder;

[0093] (7) preparing a sodium carboxymethyl cellulose solution containing disodium hydrogen phosphate, wherein the mass percentage of the disodium hydrogen phosphate is 0.65% and the mass percentage of the sodium carboxymethyl cellulose is 3.10%;

[0094] (8) The uniformly mixed powder was added into the liquid in a powder to liquid ratio of 2:1 (g / mL), stirred for 10 seconds, and solidified for 11 minutes before demolding to obtain a bone filler containing magnetic calcium salt.

[0095] The bone filler of Example 4 was tested for compressive strength. The compressive strength of the bone filler containing magnetic calcium salt was 13.52 MPa, which met the requirement of cancellous bone strength range of 2-10 MPa.

[0096] Example 5

[0097] A bone filler containing magnetic calcium salt is a φ6×12mm cylinder, which is prepared by mixing and solidifying powder and liquid in a ratio of 2:1 (g / mL);

[0098] The powder is 26% by weight of magnetic calcium salt and 74% by weight of calcium sulfate; the liquid is 1.50% disodium hydrogen phosphate sodium carboxymethyl cellulose solution, and the mass percentage of sodium carboxymethyl cellulose is 3.85%; in the magnetic calcium salt, calcium oxide accounts for 31% by weight of the magnetic calcium salt, and ferrosoferric oxide accounts for 69% by weight of the magnetic calcium salt; the particle size distribution range of the magnetic calcium salt is 2.7-45 μm; in the calcium sulfate, the mass percentage of calcium sulfate hemihydrate accounts for 92% by weight of the calcium sulfate, and the mass percentage of calcium sulfate dihydrate is 8%;

[0099] The preparation method of the bone filler in this embodiment is as follows:

[0100] (1) preparing a sodium carboxymethyl cellulose solution with a mass percentage of 3.52%, and then adding iron powder to the sodium carboxymethyl cellulose solution to prepare an iron powder suspension, wherein the mass percentage of the iron powder to the sodium carboxymethyl cellulose solution is 0.6:1;

[0101] (2) preparing a sodium hydroxide solution having a mass percentage of 25.8% and a calcium chloride solution having a mass percentage of 31%;

[0102] (3) adding 40 mL of the prepared iron powder suspension to 120 mL of the prepared sodium hydroxide solution; then adding 60 mL of the prepared calcium chloride solution to the iron powder / sodium carboxymethyl cellulose / sodium hydroxide solution at a rate of 1.5 mL / min;

[0103] (4) continuing to stir the reaction for 30 min to obtain an iron / calcium hydroxide suspension, and filtering and washing to obtain an iron / calcium hydroxide precipitate;

[0104] (5) calcining the precipitate at 560° C. for 45 min, transferring it to a dryer and cooling it to room temperature; crushing and grinding the precipitate to obtain a magnetic calcium salt with controllable particle size and morphology;

[0105] (6) uniformly mixing a certain amount of magnetic calcium salt and a certain amount of calcium sulfate to obtain a powder;

[0106] (7) preparing a sodium carboxymethyl cellulose solution containing disodium hydrogen phosphate, wherein the mass percentage of disodium hydrogen phosphate is 1.50% and the mass percentage of sodium carboxymethyl cellulose is 3.85%;

[0107] (8) The uniformly mixed powder was added into the liquid blending at a powder to liquid ratio of 2:1 (g / mL), stirred for 60 seconds, and solidified for 16 minutes before demolding to obtain a bone filler containing magnetic calcium salt.

[0108] The bone filler of Example 5 was tested for compressive strength. The compressive strength of the bone filler containing magnetic calcium salt was 14.38 MPa, which met the requirement of cancellous bone strength range of 2-10 MPa.

[0109] Example 6

[0110] A bone filler containing magnetic calcium salt is a φ6×12mm cylinder, which is prepared by mixing and solidifying powder and liquid in a ratio of 2:1 (g / mL);

[0111] The powder is 35% by weight of magnetic calcium salt and 65% by weight of calcium sulfate; the liquid is 0.56% sodium hydrogen phosphate sodium carboxymethyl cellulose solution, and the mass percentage of sodium carboxymethyl cellulose is 2.6%; in the magnetic calcium salt, calcium oxide accounts for 28% by weight of the magnetic calcium salt, and ferrosoferric oxide accounts for 72% by weight of the magnetic calcium salt; the particle size distribution range of the magnetic calcium salt is 5-45 μm; in the calcium sulfate, the mass percentage of calcium sulfate hemihydrate accounts for 89% by weight of the calcium sulfate, and the mass percentage of calcium sulfate dihydrate is 11%;

[0112] The preparation method of the bone filler in this embodiment is as follows:

[0113] (1) preparing a sodium carboxymethyl cellulose solution with a mass percentage of 6.18%, and then adding iron powder to the sodium carboxymethyl cellulose solution to prepare an iron powder suspension, wherein the mass percentage of the iron powder to the sodium carboxymethyl cellulose solution is 1.11:1;

[0114] (2) preparing a sodium hydroxide solution having a mass percentage of 22.5% and a calcium chloride solution having a mass percentage of 37.5%;

[0115] (3) adding 40 mL of the prepared iron powder suspension to 120 mL of the prepared sodium hydroxide solution; then adding 60 mL of the prepared calcium chloride solution to the iron powder / sodium carboxymethyl cellulose / sodium hydroxide solution at a rate of 9 mL / min;

[0116] (4) continuing to stir the reaction for 30 min to obtain an iron / calcium hydroxide suspension, and filtering and washing to obtain an iron / calcium hydroxide precipitate;

[0117] (5) calcining the precipitate at 570° C. for 30 min, transferring it to a dryer and cooling it to room temperature; crushing and grinding the precipitate to obtain a magnetic calcium salt with controllable particle size and morphology;

[0118] (6) uniformly mixing a certain amount of magnetic calcium salt and a certain amount of calcium sulfate to obtain a powder;

[0119] (7) preparing a sodium carboxymethyl cellulose solution containing disodium hydrogen phosphate, wherein the mass percentage of the disodium hydrogen phosphate is 0.56% and the mass percentage of the sodium carboxymethyl cellulose is 2.6%;

[0120] (8) The uniformly mixed powder was added with liquid in a powder to liquid ratio of 2:1 (g / mL), stirred for 60 seconds, and solidified for 13 minutes before demolding to obtain a bone filler containing magnetic calcium salt.

[0121] The bone filler of Example 6 was subjected to a magnetothermal test on bone cement under an alternating magnetic field of 50KHZ. The magnetothermal temperature of the bone filler containing magnetic calcium salt reached 104.1°C in 1 minute, meeting the requirement that the magnetothermal treatment temperature is greater than 40°C.

[0122] The magnetic calcium salt-containing bone filler of Example 6 was added to 2 mL of an extraction medium (MEM culture medium containing serum) at a ratio of 0.4 g and the mixture was incubated at 37±1° C. for 24±2 h to prepare an extract. The extract was taken to test the relative cell viability according to the extract test method specified in GB / T16886.5. The relative cell viability of the extract of Example 6 was 81.6%, which was greater than 70%, and had no potential cytotoxicity.

[0123] The bone filler of Example 6 was immersed in 50 ml of phosphate buffer solution, and the solution was changed every 24 hours at 37°C. Every 3 days, the bone filler was taken out, dried, weighed, and then placed in phosphate buffer solution for degradation research. Figure 5 As shown in the degradation curve, the bone filler degraded by 35.7% in 30 days.

[0124] Although the embodiments and drawings of the present invention are disclosed for illustrative purposes, those skilled in the art will appreciate that various substitutions, changes and modifications are possible without departing from the spirit and scope of the present invention and the appended claims. Therefore, the scope of the present invention is not limited to the contents disclosed in the embodiments and drawings.

Claims

1. A bone filler containing magnetic calcium salt, characterized in that: The bone filler is in block shape and is prepared by mixing and solidifying powder and liquid in a ratio of 2:1 g / mL; the powder components and mass percentages are: 61.5-81.7% calcium sulfate and 18.3-38.5% magnetic calcium salt; the liquid is a sodium carboxymethyl cellulose solution containing disodium hydrogen phosphate, the mass percentage of the disodium hydrogen phosphate is 0.16-2.52%, and the mass percentage of the sodium carboxymethyl cellulose is 1.15-4.25%.

2. The bone filler containing magnetic calcium salt according to claim 1, characterized in that: The magnetic calcium salt is a calcium oxide / ferroferric oxide complex, wherein the mass percentage of calcium oxide in the magnetic calcium salt is 22-47%, and the mass percentage of ferroferric oxide in the magnetic calcium salt is 53-78%.

3. The bone filler containing magnetic calcium salt according to claim 1, characterized in that: The particle size distribution range of the magnetic calcium salt is 2.7-83 μm.

4. The bone filler containing magnetic calcium salt according to claim 1, characterized in that: The calcium sulfate is a mixture of calcium sulfate hemihydrate and calcium sulfate dihydrate, wherein the mass percentage of calcium sulfate hemihydrate is 70-95%, and the rest is calcium sulfate dihydrate.

5. A method for preparing a bone filler containing magnetic calcium salt according to any one of claims 1 to 4, characterized in that: The steps include: Step 1, preparing a sodium carboxymethyl cellulose solution with a mass percentage of 3.28-6.52%, and then adding iron powder to the sodium carboxymethyl cellulose solution to prepare an iron powder suspension, wherein the mass percentage of the iron powder to the sodium carboxymethyl cellulose solution is (0.35-1.11):1; Step 2, preparing a sodium hydroxide solution with a mass percentage of 10.7-47.3%, and preparing a calcium chloride solution with a mass percentage of 14.2-42.5%; Step 3, adding the iron powder suspension prepared in step 1 to the sodium hydroxide solution prepared in step 2, the volume ratio of the two being 1:3; then adding the calcium chloride solution prepared in step 2 to the iron powder / sodium carboxymethyl cellulose / sodium hydroxide solution at a rate of 1.5-24 mL / min, the volume ratio of the calcium chloride solution to the sodium hydroxide solution being 1:2; Step 4, continue stirring and reacting for 20-60 minutes to obtain an iron / calcium hydroxide suspension, and filter and wash to obtain an iron / calcium hydroxide precipitate; Step 5, calcining the precipitate at 530-590° C. for 15-120 min, transferring it to a dryer and cooling it to room temperature; crushing and grinding to obtain a magnetic calcium salt with controllable particle size and morphology; Step 6, uniformly mixing a certain amount of magnetic calcium salt and a certain amount of calcium sulfate to obtain a powder; Step 7, preparing a sodium carboxymethyl cellulose solution containing disodium hydrogen phosphate, wherein the mass percentage of disodium hydrogen phosphate is 0.16-2.52%, and the mass percentage of sodium carboxymethyl cellulose is 1.15-4.25%; Step 8: Add liquid to the evenly mixed powder in a ratio of 2:1 g / mL, stir for 10 to 60 seconds, apply it to the mold with the reserved hole, and after curing for 10 to 20 minutes, demold it to obtain a bone filler containing magnetic calcium salt.

Citation Information

Patent Citations

  • Magnetic mesoporous bioactive glass drug delivery system and preparation method thereof

    CN102921010A

  • Magnetic bone cement and preparation method thereof

    CN107773784A

  • Root canal filling paste capable of being stored and injected

    CN1857190A

  • Anion substituted injectable bone cement

    KR1020090083806A

  • Porous calcium phosphate networks for synthetic bone material

    WO2005102281A2

Cited By

  • Calcium sulfate composite bone cement and preparation method thereof

    CN120617628A